Bacteriophage sensitivity of opportunistic microbiota in children with gut dysbiosis - L. A. Levanova; Yu. V. Zakharova; A. A. Markovskaya; L. Yu. Otdushkina (Фундаментальная и клиническая медицина, 2022)
Aim. As the activity of bacteriophages is species- and strain-specific, it is necessary to study bacteriophage sensitivity in distinct geographic regions with various disease patterns. Here, we aimed to study the lytic activity of specific commercially available bacteriophages against Klebsiella spp., Proteus spp., and Staphylococcus aureus isolated from the intestines of children with gut dysbiosis.Materials and Methods. Bacteriophage sensitivity was assessed in 315 opportunistic microorganisms (125 Staphylococcus aureus strains, 120 Klebsiella spp. strains, 70 Proteus spp. strains) isolated from the intestinal microbiota of 300 children < 4 years of age with gut dysbiosis. Bacteriophage preparations were produced by Microgen (Russian Federation). The lytic activity of bacteriophages was studied by a drip method on a Muller-Hinton medium by calculating the area of bacterial culture lysis.Results. We found low sensitivity of Klebsiella spp. (37.5% sensitive strains) and Proteus spp. (41.4% sensitive strains) to specific bacteriophages, albeit there were considerable differences between distinct Klebsiella species (Klebsiella pneumoniae, 56.7% sensitive strains; Klebsiella oxytoca, 18.3% sensitive strains, p = 0.03) and Proteus species (Proteus vulgaris, 52.0% strains; Proteus mirabilis, 35.6% strains, p = 0.04). Nevertheless, sensitivity to Staphylococcus aureus was considerably higher (78.4%). In addition, lytic activity of bacteriophages reduced along with the increasing severity of gut dysbiosis.Conclusion. Klebsiella spp. and Proteus spp. isolated from children with dysbiosis have low sensitivity to commercially available bacteriophages. Bacteriophage sensitivity positively correlated with gut dysbiosis.